ChatGPT application in ground settlement analysis using LISA V.8 FEA - Aco Wahyudi Efendi (Research of Scientia Naturalis, 2024)
OpenAI, an artificial intelligence research center situated in Ohio, USA, created ChatGPT. The model can be used to create autonomous discussions in conversational apps, assist with content generation, and even assist with multi-language translation with various degrees of accuracy for each language. ChatGPT is increasingly being used in all scientific domains and has a good influence, as evidenced by past research findings. This research will use ChatGPT in the field of geotechnical engineering by studying the settlement of soil layers with spongy clay type and validating it with modeling using LISA V.8 FEA finite element analysis (license). It is expected that this research will provide similar results to previous studies in engineering and other social fields. This research was conducted to be able to determine and provide validation of the behavior of the subsidence that occurred using ChatGPT and Finite Element Method Software LISA FEA V.8 from the results obtained were in model (a) there was a decrease in soil up to 0.0206 mm and in model (b) there was a decrease of 0.0167 with a ratio of 0.811 and with the ChatGPT model obtained a decrease of 0.0226 mm with a ratio of 1.097.